Child Soldiers: Victims or Offenders? - Agcaoili, Mary Grace Castillejos (Journal of Human Rights and Peace Studies, 2019)
While the Convention on the Rights of the Child has been adopted 30 years ago, the conception of childhood it introduced is often seen by developing societies as “Western.” This tension is often seen in situations where children commit crimes or are engaged in armed conflict or violent extremism. In these cases, children are often seen as both victims and offenders. While human rights advocates tend to emphasize the image that child soldiers are incapable victims of adults’ abusive compulsion, stripped from legal agency and without any accountability, some scholars believe this does not represent the child soldiers’ own perceptions of their role (Shepler, 2005). While children should primarily be considered victims under the universal application of the CRC, treating child soldiers only as victims could often be counterproductive if it prevents community reintegration and lack of self-perception (Derluyn, 2015, p. 4). The 2009 Conference on Children and Transitional Justice argued that children can be victims, witnesses and alleged offenders simultaneously. Transitional justice does not favour one model. Therefore, alternative measures for holding children accountable in a variety of legal and non-legal mechanisms should be implemented such as non-judicial accountability, amnesties, community dialogues, and juvenile justice approach. There should also be reconciliation processes where social and societal rebuilding of networks is facilitated including in humanitarian assistance while respecting the rights of the child to be reintegrated.